2014
DOI: 10.14355/fmfi.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Bioactive Peptides from Yeast Protein

Abstract: The peptides were prepared from yeast protein using yeast hydrolytic enzyme. The bioactivity of yeast peptides after impurity removal(YP1) was detected in vitro. MWCO-5kDa ultrafiltration membrane was employed to separate the yeast protein hydrolysates. Equally, the bioactivity of yeast peptides after ultrafiltration (YP2) was detected in vitro. The results showed that after ultrafiltration, bioactive components were enriched. YP2 revealed stronger superoxide anion scavenging, α-glucosidase inhibitory and ACE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…To understand the link between bioactive peptide release and protein‐encoding gene expression modulation during yest biomass propagation, an extensive search for bioactive peptides from Saccharomyces cerevisiae extracts and their diversified previously described biological effects was carried out herein and presented in Table 1 (Al‐Sahlany et al., 2020; Alcaide‐Hidalgo et al., 2007; Amorim et al., 2019; Branco et al., 2014, 2015; Branco, Francisco, et al., 2017; Branco, Kemsawasd, et al., 2017; Edens et al., 2002; Fakruddin et al., 2017; Guilloux‐Benatier & Chassagne, 2003; Hassan, 2011; He et al., 2012; Hu et al., 2014; Jung et al., 2011, 2012; Kanauchi et al., 2005; Kohama et al., 1990; Mirzaei et al., 2015; Rizk et al., 2018; Yu et al., 2002). Some of these studies provided the identification of putative bioactive peptides while others provided only peptide sequences with no association with biological activity, although they were also considered for analysis in the present study (Bener Aksam et al., 2013; Dasgupta et al., 2016).…”
Section: The Historical Use Of Yeast In Food Production—lessons From ...mentioning
confidence: 99%
See 4 more Smart Citations
“…To understand the link between bioactive peptide release and protein‐encoding gene expression modulation during yest biomass propagation, an extensive search for bioactive peptides from Saccharomyces cerevisiae extracts and their diversified previously described biological effects was carried out herein and presented in Table 1 (Al‐Sahlany et al., 2020; Alcaide‐Hidalgo et al., 2007; Amorim et al., 2019; Branco et al., 2014, 2015; Branco, Francisco, et al., 2017; Branco, Kemsawasd, et al., 2017; Edens et al., 2002; Fakruddin et al., 2017; Guilloux‐Benatier & Chassagne, 2003; Hassan, 2011; He et al., 2012; Hu et al., 2014; Jung et al., 2011, 2012; Kanauchi et al., 2005; Kohama et al., 1990; Mirzaei et al., 2015; Rizk et al., 2018; Yu et al., 2002). Some of these studies provided the identification of putative bioactive peptides while others provided only peptide sequences with no association with biological activity, although they were also considered for analysis in the present study (Bener Aksam et al., 2013; Dasgupta et al., 2016).…”
Section: The Historical Use Of Yeast In Food Production—lessons From ...mentioning
confidence: 99%
“…The peptide/free amino acid ratio, as well as protein contents and leakage degree, vary according to the extraction methodology (Rakowska et al., 2017; Takalloo et al., 2020). In vitro and in vivo assays have demonstrated that yeast extracts obtained from S. cerevisiae strains by different methodologies contain a set of peptides exhibiting distinct bioactivities (Table 1) as follows: anti‐hypertensive (Alcaide‐Hidalgo et al., 2007; Amorim et al., 2019; He et al., 2012; Hu et al., 2014; Kanauchi et al., 2005; Kohama et al., 1990; Mirzaei et al., 2015;); antimicrobial (Al‐Sahlany et al., 2020; Branco et al., 2014, 2015; Branco, Francisco, et al., 2017; Branco, Kemsawasd, et al., 2017; Fakruddin et al., 2017; Guilloux‐Benatier & Chassagne, 2003; Rizk et al., 2018); anti‐diabetes (Edens et al., 2002; Hu et al., 2014; Jung et al., 2011); anti‐obesity (Jung et al., 2012); mitogenic (Hassan, 2011); immunomodulatory (Yu et al., 2002), and antioxidant (Alcaide‐Hidalgo et al., 2007; Hassan, 2011; Hu et al., 2014; Jung et al., 2011; Mirzaei et al., 2015) (Figure 1) . Many of these bioactivities have been attributed to 22 bioactive specific amino acid sequences containing 2, 3, or 4 amino acid residues or oligopeptide short chains composed of up to 25 amino acid residues.…”
Section: Metabolic Enzymes and Stress‐enrolled Proteins As Potential ...mentioning
confidence: 99%
See 3 more Smart Citations